Testimonia greci di occorrenze dell’anapesto nella seconda sede del coliambo. Ritornando su Pers. Chol. 4 - Carmeli, Michele (Myrtia, 2020)
In v. 4 of the Choliambi the manuscript tradition gives us Heliconiadasque, which is the good reading, and, on the other hand, Heliconidasque, which is to be considered a trivialization. However, Persius’ editors often rejected the former reading, because of the presence of an anapaest in the second foot of the first metron of choliambic trimeter. So, it seemed appropriate to check if it is possible in choliambic trimeters that the single short of the first metron could admit two shorts, that is, an anapaestic resolution. Furthermore, it is important because the reading Heliconidasque seems to go against the dictates of a textual criticism rigorously based on stemmatic theory.